Iconological Study of the Experimental Film At Land (Maya Deren, 1944) - Vidaurre Arenas, Carmen Vitaliana (Eikón / Imago, 2018)
The iconological analysis of At Land (Maya Deren, 1944) allows us to identify iconographic traditions that are recovered in the short film, as well as some of the meanings, aspects of culture and ideologies related to these visual elements. Such a reading reveals the consistency of the argument of the film's plot-one that offers specific concepts of space-time and identity. In this film, chess acquires a relevant metaphorical semantics, which is coupled with the practice of creative montage, as well as the recuperation of thematic representations of the feminine in art and culture originating from a mytho- religious context. Maya Deren’s theoretical writings on film and the analysis of the film´s visual narration, from this perspective of study, also provide us with elements to separate the work of the cinematographer from some of the movements and tendencies of art and film with which dives critics have linked the cinematographic production of this avant-garde director.